Ternary systems at 298.15 K: Di-isopropylether + propanone + methanol or ethanol or propanol - Medina Naessens, Ruth Natalia (2017)
Densities ρ and viscosities η of the [di-isopropylether (DIPE) (1) + propanone (2) + either methanol, ethanol or 1-propanol (3)] ternary systems were measured at 298.15 K and at a pressure of 960 hPa using an Anton Paar DMA 500 stavigmeter. Excess molar volumes VE and viscosity deviation Δη were calculated. The calculated values were fitted by the polynomial Redlich-Kister, Nagata-Tamura and Radojković equations for ternary systems. Fourier transform infrared spectroscopy (FTIR) of the pure components and mixtures of the [DIPE (1) + propanone (2) + either methanol, ethanol or 1-propanol (3)] ternary systems at 298.15 K was performed. From the analysis of the results it is possible to propose the molecular interaction mechanisms in ternary mixtures.